2014
DOI: 10.1245/s10434-014-3677-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Metastasectomy Secondary to Esophageal Carcinoma: Long-Term Survival and Prognostic Factors

Abstract: Pulmonary resection for lung metastases from esophageal carcinoma should be considered in selected patients, and repeated metastasectomy should be encouraged. Extrapulmonary metastases before pulmonary metastasectomy, poor differentiation of primary esophageal carcinoma, and short DFI are unfavorable prognostic factors. Due to poor prognosis, metastasectomy in patients with these factors should be more carefully considered before being indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 11 publications
3
29
1
Order By: Relevance
“…The cumulative survival for patients without a history of extrapulmonary metastasis between initial treatment and pulmonal recurrence was 40.7% at 5 years, while the patients with well and moderately differentiated SCC had significantly prolonged survival compared to those with poor differentiated primaries ( p < 0.01). DFI of > 12 months was showed as another favorable prognostic factor (median survival with DFI > 12 months and DFI < 12 months was 43.7 and 24.7 months, respectively, p = 0.02) [ 18 ]. The largest published series is the one reported by Shiono et al, including 49 patients who underwent metastasectomy (48 cases with SCC, 1 case with adenocarcinoma), 39 of whom with solitary metastases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulative survival for patients without a history of extrapulmonary metastasis between initial treatment and pulmonal recurrence was 40.7% at 5 years, while the patients with well and moderately differentiated SCC had significantly prolonged survival compared to those with poor differentiated primaries ( p < 0.01). DFI of > 12 months was showed as another favorable prognostic factor (median survival with DFI > 12 months and DFI < 12 months was 43.7 and 24.7 months, respectively, p = 0.02) [ 18 ]. The largest published series is the one reported by Shiono et al, including 49 patients who underwent metastasectomy (48 cases with SCC, 1 case with adenocarcinoma), 39 of whom with solitary metastases.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed before, short DFI is negatively correlated with survival [ 20 ], and long DFI is considered as a favorable prognostic factor for overall survival of both surgical and non-surgical groups [ 7 ]. Kobayashi et al and Shiono et al suggested a DFI > 12 months as a statistically significant favorable prognostic factor for pulmonary metastasectomy ( p < 0.05) [ 18 , 19 ]. With regard to pulmonary recurrence, long DFI is noted to be a favorable prognostic factor from the International Registry of Lung Metastases, but many different tumor types have been assessed in this study [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiono et al [7] reported a 5-year OS rate of 30 % and that the survival of patients with DFI <12 months was significantly lower than in patients with DFI >12 months. Kobayashi et al [11] also recently reported that extrapulmonary metastasis before pulmonary metastasectomy, poor differentiation of primary esophageal cancer, and short DFI are unfavorable prognostic factors. Furthermore, Takemura et al [10] showed that surgical intervention for metachronous pulmonary metastasis is an acceptable treatment option in selected patients without extrapulmonary metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…Although the most common sites of distant hematogenous metastasis are the lung, liver, bone, and brain, there have been several studies on therapies for pulmonary metastasis after curative resection of esophageal cancer [6][7][8][9][10][11]. In the current study, we focused on the role of resecting metachronous pulmonary metastases of thoracic esophageal cancer at a single institution.…”
Section: Introductionmentioning
confidence: 99%